Feasibility Study of Integrated Arabic Bilingual Book at Islamic Elementary School - Putri, Neli; Febriani, Suci Ramadhanti; Mustika, Dela; Yassirli, Ulfa; Bedra, Kddour Guettaoi (Syarif Hidayatullah State Islamic University of Jakarta, Indonesia, 2023)
The book “I Love Arabic” is a learning resource used in Arabic lessons for Class IV Dâr El-Iman Islamic Elementary School in Padang. This book is based on a bilingual system, namely by presenting Arabic and English study materials. This bilingual Arabic book is still a new category, so the content and presentation of the material need to be analyzed for its feasibility and suitability aspects with the character of bilingual books and the demands of the applicable curriculum. This study aims to analyze the bilingual book from the perspective of the feasibility of its content and presentation. This library research used a qualitative approach with secondary data. The main reference used the Bilingual Book “I Love Arabic & English” Class IV Dâr El-Iman Padang textbooks and other relevant additional references. Data was collected through recording documentation in observation and content analysis. The data analysis technique used follows Miles and Huberman. The results identified: First, the content qualifications of the bilingual book “I Love Arabic & English” Class IV published by Dâr el-Iman are in the very proper category with a score of 75%. Second, the presentation of the material is in a feasible category with a percentage score of 65%. This book still needs to be refined to suit the character of a bilingual-based textbook.